Dynamic governance model in tourism village development: Soft systems methodology approach - Roekminiati, Sri; Hara, Abubakar Eby; Suryawati, Dina; Oktawirani, Panca (Edelweiss Applied Science and Technology, 2026)
The development of tourism villages is an important strategy for improving the welfare of rural communities through the sustainable utilization of local potential. However, the ever-changing environmental dynamics, fluctuations in tourist visits, and the complexity of inter-actor relationships necessitate adaptive and responsive governance. Ketapanrame Tourism Village, Mojokerto Regency, is one of the destinations that has experienced rapid growth but still faces various governance issues, such as the absence of standard operating procedures, limited human resource capacity, and weak integration of external networks. These conditions highlight the need to formulate a governance model capable of navigating the complexity and uncertainty in tourism village management. This study aims to develop a dynamic governance model for Ketapanrame Tourism Village using the Soft Systems Methodology (SSM) approach. This approach helps understand unstructured problem situations, map stakeholder perspectives, and formulate a conceptual model that is systematically desirable and culturally acceptable. Data were collected through in-depth interviews, field observations, document analysis, and focused discussions with the village government, BUMDes, KUB, destination managers, and the community. The study’s findings indicate that the root causes of governance problems in tourism villages are primarily due to three aspects: weak adaptive policies, low adaptive capacity of implementers, and suboptimal external networks. Based on the SSM analysis, the study proposes the A2ER (Adaptive Policy, Adaptive Capabilities, and External Reliance) model as a dynamic governance framework. This model offers guidance for strengthening data-driven policies, enhancing innovation and human resource capacity, and fostering cross-sector collaboration. The research contributes to the theoretical understanding of tourism village governance and provides practical recommendations for sustainable tourism village management.